Analyze Netizen Sentiment on the Shopee Application - Denica Emilia Vernanda (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2023)
Internet users in Indonesia continue to grow yearly, with the number of users in 2020 reaching 160 million. Most people access social media, primarily buying and selling e-commerce platforms. Based on data from the Play Store in 2020, Shopee is ranked first as the most frequently used e-commerce application. Seeing this phenomenon, a goal was formed to examine the sentiment of netizens towards the Shopee application. Researchers chose qualitative methods with extensive data analysis assisted by NVIVO applications to achieve this goal. This study uses secondary data by looking at the research unit in the form of comments in the application comment column on Google Play by text mining. The results of this study are that 52.39% of Shopee users give negative comments, 41.26% positive comments, and 6.35% neutral comments, so it can be concluded that Shopee still has many shortcomings that must be corrected to provide the best service to the user community. Keyword: Netizen sentiment; big data; text mining